Successful management of hair follicles following urethroplasty with holmium:YAG laser epilation: A case report - Sancı, Adem; Gülpınar, Başak; Gülpınar, Ömer (Journal of Surgery and Medicine, 2019)
A 27-year-old male presented with recurrent urinary tract infections, calculus formation and hair follicles in urine following urethroplasty. The patient was treated with urethroscopic holmium laser in 2012, which was performed by Beiko for the first time in the literature to remove stones and epilate hair follicles. At 3-month, 3-year and 6-year follow-ups, the patient was symptom and infection-free. Urethrocystoscopy was performed in the 6-year follow-up, and no stone formation was observed. There were only a few hair follicles that were too short to require re-surgery. Urethral hair follicles and stone formation are uncommon long term complications following urethroplasty. Endoscopic holmium laser hair epilation is a rarely performed treatment option for hair follicles and urethral stone. Holmium:YAG laser epilation may be an alternative, minimally invasive treatment option with successful long term outcomes.